Borderline-High Mean Corpuscular Volume Levels Are Associated with Arterial Stiffness among the Apparently Healthy Korean Individuals - Kwon, Haneul (Korean J Fam Med, 2020)
BACKGROUND: High mean corpuscular volume (MCV) has been implicated in various health problems, such as anemia, liver disease, and thyroid disease. However, the clinical significance of borderline-high MCV is poorly understood in the primary care setting. This study aimed to investigate whether borderline-high MCV was related to arterial stiffness in Korean adults as measured by brachial-ankle pulse wave velocity (baPWV). METHODS: This cross-sectional study comprised 582 participants aged >30 years who underwent routine health examinations. Borderline-high MCV was defined as over 95.0 fl (>90th percentile) after excluding participants with MCV of ≥100 fl or ≤80 fl, and high baPWV was defined as >1,600 cm/s (>90th percentile). The odds ratios (ORs) and 95% confidence intervals (CIs) for high baPWV according to borderline-high MCV were calculated using multiple logistic regression analyses after adjusting for the confounding variables. RESULTS: The mean age of the study population was 47.8±11.7 years, and 56.9% of the participants were male. Compared to that in the control group, the OR (95% CI) of high baPWV in those with a borderline-high MCV was 3.68 (1.39–9.74) after adjusting for age, sex, body mass index, alcohol intake, smoking status, regular exercise, mean blood pressure, fasting plasma glucose, triglyceride, high-density lipoprotein cholesterol, C-reactive protein, γ-glutamyltransferase, uric acid, hypertension medication, and diabetes medication. CONCLUSION: Borderline-high MCV was independently associated with arterial stiffness among apparently healthy Korean individuals.